E-scooter attitudes and risk-taking behaviours: an international systematic literature review and survey responses in the West Midlands, United Kingdom - Burt, Nathalie; Ahmed, Zubair (Frontiers in Public Health, 2023)
SEE MANUSCRIPT Introduction: Micromobility initiatives, including electric scooters (e-scooters), are part of the UK government’s sustainability drive. Since summer 2020, multiple trials have been conducted across the UK. Safety concerns have been raised around e-scooters joining other vehicles on UK roads, alongside the numerous private e-scooters illegally ridden on public land. Although literature has been published abroad on perceptions, risk-taking behaviours and attitudes surrounding e-scooters, independent UK research has concentrated on analysing trauma. Our aim was to identify common themes and recommendations to form conclusions on factors affecting e-scooter trauma hospital admissions. Methods: A systematic literature search in June 2023 extracted studies focused on the primary outcomes of risk factors, perceptions, and attitudes surrounding e-scooters globally from the EMBASE, PubMed and MEDLINE databases. Two independent reviewers conducted a critical appraisal to extract potential biases and study characteristics. A critical appraisal skills programme (CASP) analysis was also completed. Two surveys distributed in Birmingham and Wolverhampton focused on: public perception towards e-scooters, and road user attitudes around e-scooters. The surveys were opened in late-March 2023 and closed in late-July 2023. Results: 443 studies were retrieved with 13 studies being eligible according to our inclusion and exclusion criteria. Various qualitative methods of data collection were used. The CASP assessment concluded that the studies were of good quality. Their heterogeneity meant sample sizes could not be meaningfully aggregated. Many studies focused on safety concerns. Others reviewed and observed risk-taking behaviour, non-rider perceptions, and infrastructure. Our surveys received 153 and 146 responses, respectively. Observed and reported risk-taking behaviours included pavement riding, alcohol consumption, and low helmet use. However, respondents gave positive opinions on e-scooter convenience but raised concerns regarding rider and non-rider safety. Discussion: E-scooters were perceived as a sustainable form of transport; however, safety concerns were raised. Our research points to risk-taking behaviours by riders being associated with admissions into hospital emergency departments. We conclude that well maintained infrastructure could improve the safety of both e-scooter riders and vulnerable pedestrians, whilst education and enforcement of clear rules may reduce risk-taking behaviour. Furthermore, hospital data and future studies should differentiate between private and rental e-scooters.